(untitled) (LEARNing Landscapes, 2024)
This commentary presents six pieces from the Que du Love (Only Love) exhibition, which was led by photographer Amelia Segrera and Chalet Kent staff, multimedia director Marilia Beltrame, interviewer and writer Fabiana Diaz, and curator Karl-André St-Victor. The five original photographs featured here were taken on 35 mm film by Segrera, and each features a young person accompanied by their words about love, which are excerpts taken from their interviews. We also include three poems, in French, from student Rania Guerasse, exploring some of the visceral and spiritual intensities of love and heartbreak.